2019
DOI: 10.21273/hortsci13772-18
|View full text |Cite
|
Sign up to set email alerts
|

Sexual and Apomictic Seed Reproduction in Aronia Species with Different Ploidy Levels

Abstract: The genus Aronia Medik., also known as chokeberry, is a group of deciduous shrubs in the Rosaceae family, subtribe Pyrinae. The four commonly accepted species include A. arbutifolia (L.) Pers., red chokeberry; A. melanocarpa (Michx.) Elliott, black chokeberry; A. prunifolia (Marshall) Reheder, purple chokeberry; and A. mitschurinii (A.K. Skvortsov & Maitul). Wild and domesticated Aronia species are found as diploids, triploids, and tetraploids. Genetic improvement of polyploid Aronia genotypes has been limited… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 28 publications
0
5
0
Order By: Relevance
“…Samples were stored in a -80°C freezer until DNA extraction. Genomic DNA was extracted and AFLP reactions were carried out following the protocol outlined in Mahoney et al (2019). Quality and concentration of extracted DNA were measured using a spectrophotometer (NanoDrop-1000; Thermo Scientific, Willington, DE).…”
Section: Methodsmentioning
confidence: 99%
“…Samples were stored in a -80°C freezer until DNA extraction. Genomic DNA was extracted and AFLP reactions were carried out following the protocol outlined in Mahoney et al (2019). Quality and concentration of extracted DNA were measured using a spectrophotometer (NanoDrop-1000; Thermo Scientific, Willington, DE).…”
Section: Methodsmentioning
confidence: 99%
“…AFLP markers have previously been used in Aronia because of their high frequency of polymorphisms and reproducibility (Leonard et al, 2013;Mahoney et al, 2019). In addition, Leonard et al (2013) demonstrated that AFLP markers can be used across Aronia, Pyrus, and other closely related taxa.…”
Section: Discussionmentioning
confidence: 99%
“…DNA extraction and amplified fragment length polymorphism (AFLP) procedure. Genomic DNA was extracted following the protocol outlined in Mahoney et al (2019). The quality and concentration of extracted DNA were determined using a NanoDrop-1000 spectrophotometer (Thermo Scientific, Willington, DE).…”
Section: Methodsmentioning
confidence: 99%
“…Skvortsov & Maitul) (tetraploid) and it is used in commercial fruit production, usually as the cultivars ‘Viking’ or ‘Nero’ [ 3 ]. Diploid A. melanocarpa reproduce sexually and are most commonly found in the Northeastern United States, primarily in the New England region [ 4 , 5 ]. These fruits can easily be identified by the presence of dark-colored fruits in mid- to late summer.…”
Section: Introductionmentioning
confidence: 99%